2018
DOI: 10.1088/1748-9326/aadbb9
|View full text |Cite
|
Sign up to set email alerts
|

The strengthening of Amazonian precipitation during the wet season driven by tropical sea surface temperature forcing

Abstract: Amazonian rainfall plays a critical role in the global climate system and the hydrological cycle. It is thus important to quantify changes in the Amazonian rainfall and clarify its mechanism. Previous studies indicate that the interannual variability of Amazonian precipitation could be largely attributed to variabilities in the South American monsoon system and the El Niño Southern Oscillation. However, the trend of the wet season tropical Amazonian precipitation during recent decades is not very well investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 63 publications
6
57
0
1
Order By: Relevance
“…Here, we found that the combined AMO-PDO conditions and the associated interbasin cell between the equatorial Atlantic and eastern equatorial Pacific are crucial factors in defining the variations in the Walker cell. The analyses here provide additional arguments to interpret the recent findings on the increase of the Amazonian rainfall during the wet season over the 1979-2015 period (Wang et al, 2018) and on the intensification of flooding extremes over the 1903-2015 period (Barichivich et al, 2018). Wang et al (2018) attributed their results to the Atlantic warming, which intensified the moisture transport convergence over tropical SA.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Here, we found that the combined AMO-PDO conditions and the associated interbasin cell between the equatorial Atlantic and eastern equatorial Pacific are crucial factors in defining the variations in the Walker cell. The analyses here provide additional arguments to interpret the recent findings on the increase of the Amazonian rainfall during the wet season over the 1979-2015 period (Wang et al, 2018) and on the intensification of flooding extremes over the 1903-2015 period (Barichivich et al, 2018). Wang et al (2018) attributed their results to the Atlantic warming, which intensified the moisture transport convergence over tropical SA.…”
Section: Discussionmentioning
confidence: 59%
“…The analyses here provide additional arguments to interpret the recent findings on the increase of the Amazonian rainfall during the wet season over the 1979-2015 period (Wang et al, 2018) and on the intensification of flooding extremes over the 1903-2015 period (Barichivich et al, 2018). Wang et al (2018) attributed their results to the Atlantic warming, which intensified the moisture transport convergence over tropical SA. On the other hand, Barichivich et al (2018) argued that the intensified floods were related to the strengthening of the Walker circulation, which, in turn, resulted from the Atlantic warming and tropical Pacific cooling.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This means that in years with significant ENSO events, rainfall regime tends to increase in this region, which implies increased rainfall erosivity and, so, sediment rates. Accordingly, Figure 5b shows the positive change in amount rate of the precipitation during the six different months (DJFMAM) from 1979-2015 on most of the Amazon basin, and with spatial range from 30 to 100 mm per season [91]. Marengo and Espinoza Villar [36] also found that hydrological data show trends towards more extreme events across the Amazonia region during the 20th century.…”
Section: River Sediment Discharge Historical Reconstructionmentioning
confidence: 87%
“…Therefore, the concentration of daily rainfall is a subject of great interest, since it is highly associated with the contribution of extreme precipitation (%) of certain time durations, during several days, to the total rainfall amount of the defined time interval (Alijani et al, 2008;Zhang et al, 2009;Suhaila and Jemain, 2012;Shi et al, 2013;Zubieta et al, 2017a). This point is particularly relevant in the AB, where an increase of rainy (dry) days has been identified in the north (south) part of the basin since the last two decades (e.g., Espinoza et al, 2018;Wang et al, 2018).…”
mentioning
confidence: 99%